Educational motivation of the senior students of Dental faculty - V. B. Lampusova; L. Yu. Orekhova; L. I. Shalamay (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2020)
Introduction. The question of learning motivation turns out to be the leading one in psychology of study. The content and structure of motivation form a certain motivational level of a student as well as the degree of his educational activity. During the years of study at the university, the correlation of motives changes, influencing the academic progress of the students.The objective of our study was to investigate the motivation peculiarities of educational activity in 4th year-students of the Faculty of Dentistry.Methods and materials. Forty-eight 4th year – students of the Faculty of Dentistry were analyzed for the structure of their motivation to study. The techniques and methods used in the study were «Studying the motives of students` learning activities» by A. A. Rean and V. A. Yakunin, «Motivation for university education» by T. I. Ilyina, «Motivation for success» and «Motivation to avoid failures» by T. Ehlers.Results. The learning activity of dental students is supported by many motives. The strongest leading motives are professional, educational, and cognitive motives as well as motivation for obtaining a diploma. The motivational sphere of students embraces both external and internal motives that do not depend on external stimuli. The students are equally aimed at gaining knowledge and mastering the profession. In the sphere of motivation, the students have both motivations for achieving success, and the motives for avoiding failures. The methods of forming positive learning motivation in the classes of 4-year dentistry students are given.Conclusion. The educational activity of dental students is supported by professional, educational, cognitive, and pragmatic motives. The structure of motivation includes both external and internal motives that give it stability. Students are satisfied with their chosen profession, and their educational activities are not compelled. The dental students have motivations for archiving success and the motives for avoiding failures, expressed to a greater extend. It must be taken into account in motivational support.Authors declare no conflict of interest.The authors confirm that they respect the rights of the people participated in the study, including obtaining informed consent when it is necessary, and the rules of treatment of animals when they are used in the study. Author Guidelines contains the detailed information.